Pembiayaan dan Usaha Mikro, Kecil Dan Menengah (UMKM) Terhadap Lembaga Keuangan Mikro Syariah (LKMS) - Wahiddudin, Mohammad (Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
This study aimed to determine the financing and MSMe on Sharia Microfinance.  The population in this research are all Sharia Microfinance in Indonesia 2016-2018. The research method that is used in this study is explanatory research method. The method of data analysis that is used in this research is multiple linear regression analysis. The results of this study indicate that financing partially able to explain the variable Sharia Microfinance; MSMe partially unable to explain the variable of Sharia Microfinance.  Simultaneously financing and MSMe influenced on Sharia Microfinance.